GOVERNANCE AND PERFORMANCE OF VILLAGE-OWNED ENTERPRISES (BUMDES) - Sigit Kurnianto; Budiharjo Iswanu Iswanu (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aims to examine the effect of governance on the performance of village-owned enterprises. The governance variable consists of 6 principles, namely transparency, accountability, cooperation, participation, emancipation and sustainability. Organizational performance includes financial and non-financial performance. This study uses quantitative data with primary data sources. The research data comes from questionnaires distributed online and offline to village-owned enterprises administrators in East Java. Quantitative data were processed using SPSS 25 software. The hypothesis in this study was tested using simple linear regression. The results of this study found that governance has a positive and significant influence on the performance of village-owned enterprises organizations in the East Java region. This finding is expected to provide a reference in Good Governance for BUMDes in Indonesia. Armed with the knowledge gained from this research, it is hoped that local governments will improve the governance and performance of BUMDes. In addition, the BUMDes Management is expected to improve organizational performance which is assessed both in terms of financial and non-financial through good governance of BUMDes.